The role of cultural precincts as major tourism development initiatives in city centres. Case study : Newtown, Johannesburg City Centre - Ngwenya, Nonhlanhla Florence (My University, 2018)
As urban regeneration is increasingly taking place in many countries in the world, the question of developing inner cities through cultural tourism is acquiring more significance. Urban regeneration is capable of producing the economic benefits of the city. It also has the potential of improving the physical environment of the city, the image of the city and the welfare of the residents in the city centre. Hence many cities in the developing and developed countries have amongst other things adopted the cultural tourism led approaches to regenerate their cities. The development of cultural precincts in city centres with the intention of promoting cultural tourism has played a significant role in the development of local economic strategies. This research begins by examining how has the concept of cultural precinct been developed, how has it been implemented and how successful it has been in the so called ‘best practice’ model. Secondly, the research focuses on the formation of Newtown Cultural Precinct and its role as a tool for urban regeneration in the Johannesburg city center. It also explores the criteria for cultural precincts in terms of international best practice and whether Newtown meets these requirements. The first two chapters look at tourism background, the methodology used to carry the study, the literature behind urban regeneration, cultural tourism, the formation of Cultural Precincts and lastly Tourist Policy and Organisation. The third chapter focuses on the formation of Newtown cultural precinct, its infrastructure and architecture, heritage and cultural activities, marketing and promotions of cultural activities and lastly nightlife in both cultural precincts Newtown and U-Street. The fourth chapter which is the core of the study discusses and analyses the findings of the research with regards to whether Newtown meets the criteria of the world’s best practice model as a cultural precinct by making use of U-Street in Washington DC and Bristol in the UK as a measuring stick. The study concludes with some more general comments and recommendations in Chapter 5 as to how these goals can be realised through the implementation of Newtown Cultural Precinct, for the benefit of all sectors of the economy.
A research report submitted to the Graduate School of Humanities, Social Sciences and Education, University of the Witwatersrand, Johannesburg, towards the degree of Master of Arts by Course work (Cultural and Heritage Studies) Johannesburg, July 2018
Keywords: Tourism--South Africa; Heritage tourism--South Africa; Heritage tourism